HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN KESEIMBANGAN DINAMIS PADA KOMUNITAS LANSIA WANITA DI DAHLIA SENJA LIMO - Muhamad Dwi Yudha Satya (2023)
Background: In old age, the physical activity of the elderly decreases, this causes a decrease in dynamic balance in the elderly. Disturbed dynamic balance can increase the level of risk of falling in the elderly. Purpose: The aim of this study was to determine the relationship between physical activity and dynamic balance in elderly women in the Dahlia Senja Limo Community, Depok. Purpose: The aim of this study was to determine the relationship between physical activity and dynamic balance in elderly women in the Dahlia Senja Limo Community, Depok. Design: The design of this study used a cross-sectional method with measurement methods using the International Physical Activity Questionnaire Short Form (IPAQ-SF) to measure physical activity levels and the Timed Up and Go Test (TUG) to measure dynamic balance levels. The sample in this study were the elderly in the Dahlia Senja Limo Depok Elderly Community, totaling 40 samples Research Results: Based on the results of the Spearman's rho test, it is known that the value of p: 0.026 where p <0.05 and it is known that the correlation coefficient is 0.351. The results of this analysis show that there is a significant positive correlation between physical activity and dynamic balance in elderly women in the Dahlia Senja Community.